P6.038 Technical Support For Clinical Services of a Large Scale HIV Prevention Programme For Key Populations in India. (13th July 2013) - Das, A; Parthasarathy, M; Narayanan, P; Wi, T; Kumta, S; Dallabetta, G
Abstract : Background: Avahan was a focused HIV prevention programme implemented across six states in India by seven lead agencies through 129 local NGOs, providing services to 321, 000 individuals from key populations. Clinical services for STIs were an important component of Avahan's intervention package. Methods: Technical support was provided by a centralised agency to lead agencies' STI staff who directly supervised NGO clinical services. The approach during the first phase (2005–2009) of 'build and operate' included developing standardised guidelines, training, quality assurance and quality improvement, and using monitoring data to improve the programme. During the final phase (2009–2013) of transitioning to government support, the strategy was to ensure that services were restructured to align with national guidelines, generate and provide evidence towards advocacy for improvement of the national programme. Results: In 2005–2009, 431, 434 individuals made 2.7 million clinic visits. The annual average number of clinic visits by individuals increased from 1.6 to 3.5, and the proportion of visits for STI syndromes decreased from 52.5% to 11.8%. Verbal screening for tuberculosis (TB) identified 6, 879 TB suspects of whom 1, 565 were diagnosed with active TB. The quality monitoring of Avahan clinics showed an increased score from 2.21 to 3.82 (on a scale of 0–5). The introduction of a point of care test for syphilis doubled the proportion of clinic attendees screened from 2007 to 2009. In the transition phase, revised operational guidelines were developed to align with national guidelines and a nurses' training was conducted to address 'task shifting'. The national programme adapted the Avahan guidelines for STI management among key populations. Conclusion: A centralised technical support agency has a pivotal role in ensuring standardised and high quality services. Large scale and national programmes would benefit from collaborating with independent technical units to outsource some of the work of implementation.